Compound K induces neurogenesis of neural stem cells in thrombin induced nerve injury through LXRα signaling in mice. (11th June 2020) - Zhou, Li; Yang, Fan; Yin, Jie-wen; Gu, Xi; Xu, Yue; Liang, Yue-qin
Highlights: Compound K promotes neurogenesis, proliferation and reduces apoptosis of endogenous neural stem cells (EnNSCs) after induction by thrombin. Compound K treatment increases the neurogenesis of EnNSCs through liver X receptor α (LXRα) signaling pathway. Compound K improves the neurogenesis of subventricular zone (SVZ), myelin repair and behavioral deficit after stereotaxic injection of thrombin in the basal ganglia of mice, and this process involved LXRα. Abstract: Intracerebral hemorrhage (ICH) causes neurological function deficit due to the loss of neurons surrounding the hematoma. Increased neurogenesis of endogenous neural stem cells (EnNSCs) is believed to increase cell proliferation and differentiation, thereby improving the neurological deficit. However, there are still limited drugs that are effective for treating neurological deficit. So, the effects of compound K (CK) in EnNSCs were measured after thrombin-induced mice models both in vivo and in vitro, and investigated the probable mechanisms of CK during pro-neurogenesis. The results revealed that 10 μM CK promotes neurogenesis, proliferation and reduces apoptosis of EnNSCs after induction by thrombin. After that, CK treatment increased the neurogenesis of EnNSCs through liver X receptor α (LXRα) signaling pathway using adeno-associated virus knockdown and knocked out mice of LXRα gene. Finally, intraperitoneal injection of 10 mg/kg CK improved the neurogenesis of subventricular zone (SVZ), myelin repair and behavioral deficit after stereotaxic injection of thrombin in the basal ganglia of mice, and this process involved LXRα. These observations provided evidence regarding the effect of CK in pro-neurogenesis via LXRα activation, and suggested further evaluation of it due to its potential role as an effective modulator in the treatment of ICH.